English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

express the given quanity as a single logarithim

ln x +(a ln y) - (b ln z)

2007-01-15 16:56:34 · 4 answers · asked by Chris 1 in Science & Mathematics Mathematics

4 answers

ln x +(a ln y) - (b ln z)
Since
ln (a b)=ln(a) + ln(b)
and
ln(x^a)= a ln(x)

We have

ln(x)+ ln(y^a) – (ln(z^b)=

=ln((x y^a )/z^b)

2007-01-15 17:20:58 · answer #1 · answered by Edward 7 · 0 0

ln is just log with a subscript of e

Use these properties to help you in your problems in logarithms.
(I have restated these properties with ln for the convenience of this problem)

(1) ln(ac)=ln(a)+ln(c)
(2) ln(a/c)=ln(a)-ln(c)
(3) ln(a^R)= Rln(a)
(4) ln(1/c)=-ln (c)

ln(x) + Aln(y) -Bln(z)

Using (3) on the 2nd and 3rd terms we arrive at:

ln(x) + ln(y^a) -ln(z^B)

Using (1) on the 1rst and 2nd terms:

ln(x*y^a) - ln(z^B)

Using (2) on the remaining two terms

ln((x*y^a)/ (z^b))

Forgive my use of capitals. It doesn't look right to me while I'm doing the problem.

Need more help?
IM me

2007-01-16 01:36:36 · answer #2 · answered by NightWindZero 2 · 0 0

ln x + (a ln y) - (b ln z) =
ln x + ln(y^a) - ln(z^b) =
ln((xy^a)/(z^b))

2007-01-16 01:23:03 · answer #3 · answered by Helmut 7 · 0 0

ln[xy^a/z^b]

2007-01-16 01:00:20 · answer #4 · answered by raj 7 · 0 0

fedest.com, questions and answers